1996
DOI: 10.1073/pnas.93.4.1607
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of a Rrp1 transgene reduces the somatic mutation and recombination frequency induced by oxidative DNA damage in Drosophila melanogaster.

Abstract: Recombination repair protein 1 (Rrpl) includes a C-terminal region homologous to several DNA repair proteins, including Escherichia coli exonuclease III and human APE, that repair oxidative and alkylation damage to DNA. The nuclease activities of Rrpl include apurinic/apyrimidinic endonuclease, 3'-phosphodiesterase, 3'-phosphatase, and 3'-exonuclease. As shown previously, the C-terminal nuclease region of Rrpl is sufficient to repair oxidative-and alkylationinduced DNA damage in repair-deficient E. coli mutant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 40 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…), and overexpression of Ref1 protein in Drosophila protected cells from genotoxic oxidative stress (Szakmary et al . ), whereas downmodulation of Ref1 caused hypersensitivity to oxidative damage (Walker et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), and overexpression of Ref1 protein in Drosophila protected cells from genotoxic oxidative stress (Szakmary et al . ), whereas downmodulation of Ref1 caused hypersensitivity to oxidative damage (Walker et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have found that reactive oxygen species-mediated activation of Ref1 involved two steps, namely Ref1 translocation from the cytoplasm to the nucleus (Merluzzi et al 2008) and de novo protein synthesis via transcriptional activation of the Ref1 promoter (Tell et al 2005). It has been shown that oxidative stress (such as H 2 O 2 ) caused a translocation of APE/Ref1 from the cytoplasm to the nucleus or to mitochondria (Frossi et al 2002), and overexpression of Ref1 protein in Drosophila protected cells from genotoxic oxidative stress (Szakmary et al 1996), whereas downmodulation of Ref1 caused hypersensitivity to oxidative damage (Walker et al 1994). Furthermore, different oxidative agents have been shown to promote a transient increase in Ref1 at both the mRNA and protein levels in vitro and in vivo (Fritz et al 2003), which was accompanied by an adaptive response (protective) of cells to the cytotoxic and clastogenic activity of oxidative agents (Qu et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Using GST pulldowns, we showed that Rrp1 requires the presence of Ser 42 to be able to interact efficiently with PSI. Rrp1 is an exonuclease that is involved in DNA damage repair [31]. Connections between splicing and DNA repair have been previously recognized [32].…”
Section: Discussionmentioning
confidence: 99%
“…Our results confirmed that the AdoR 1 and AdoR KG03964ex mutations have no negative effect on fly viability under standard rearing conditions. AdoR 1 strongly reduces wts x1 clone frequency in SMART In order to examine the effect of the loss of AdoR function on the incidence of somatic mosaic clones in flies in vivo, we adapted a robust test, originally designed for assaying the mutagenicity of chemicals, or the effect of genetic background on the frequency of mutations [25,26]. The mutations are visualized as somatic mosaic clones generated by LOH of the recessive allele of the marker gene.…”
Section: Ador Mutant Flies Are Homozygous Viablementioning
confidence: 99%